Farm forestry Potential in Andhra Pradesh - Ramakrishna Rao, N. (Indian Forester, 1994)
Large extent of marginal private lands occur in Andhra Pradesh. Together with field bund/field perimeter, the farmlands offer a great potential for tree growing. Past experience in the State has shown that Farm Forestry is the only way to bring about self suffieiency in wood and wood products. However. Success of the programme largely depends on the extension and marketing support.